PENINGKATAN EFISIENSI PRODUKSI DAN DAYA SAING PRODUK OLAHAN LORJUK SEBAGAI OLEH-OLEH KHAS MADURA DESA POLAGAN KECAMATAN GALIS KABUPATEN PAMEKASAN - Trisyani, Ninis; Hidayat, Moh. Taufiq; Agustin, Titik Indhira Agustin Indhira (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
Pamekasan is one of the districts whose coastal areas produce bamboo shells or locally known as "Lorjuk". The processed Lorjuk to be products for Pamekasan's typical souvenirs is potentially very large because the bamboo shells can not be found on all beaches around Indonesia. One of the efforts to increase the competitiveness of processed Lorjuk products as typical Madurese souvenirs is to increase production efficiency to spur the economy of the Lorjuk processing community on “Pesisir Biru” in Polagan Village, Galis District, Pamekasan Regency. Nevertheless, the problem is a lack of knowledge about Lorjuk processing techniques and attractive packaging methods and a lack of understanding the business analysis and marketing efficiency. The offered solution is to carry out training on attractive processing techniques and packaging methods, PIRT permits, and on marketing techniques for the Lorjuk processed business as a Pamekasan's typical souvenirs. Solving partner problems is by implementing a marketing mix model that focuses on products and promotions. The result of the first activity is that the Lorjuk processors gain knowledge on the Lorjuk characteristics from Pamekasan and the kinds of processed products for souvenirs and the packaging techniques. The second activity is to provide training on Lorjuk processing techniques and product packaging, e.i. “Sambal Lorjuk”. The third activity is to calculate the cost analysis and marketing the products virtually via social media such as “Buka Lapak" and Facebook.